Preliminary Survey and Awareness for Otter Conservation in Rupa Lake, Pokhara, Nepal - Bhandari, Jyoti; GC, Dhruba Bijaya (Journal of Wetlands Ecology, 2008)
DOI: 10.3126/jowe.v1i1.1570 No abstract. Journal of Wetlands Ecology Vol.1(1/2) 2008, p.2